PD-1/PD-L1 Checkpoint Inhibitors in Tumor Immunotherapy - Liu, Jinhua; Chen, Zichao; Li, Yaqun; Zhao, Wenjie; Wu, JiBiao; Zhang, Zhen (Frontiers in Pharmacology, 2021)
Programmed cell death protein 1 (PD-1) is a common immunosuppressive molecule on the surface of T cells and plays an important role in downregulating the immune system and promoting self-tolerance. Its ligand programmed cell death ligand 1 (PD-L1) is overexpressed on the surface of a variety of malignant tumor cells, where it binds to PD-1, inhibits the proliferation of PD-1-positive cells, and participates in the immune escape of tumors leading to treatment failure. The PD-1/PD-L1-based pathway is of great value in immunotherapy of cancer and has become an important immune checkpoint in recent years, so understanding the mechanism of PD-1/PD-L1 action is important for immune combination therapy and patient prognosis. PD-1/PD-L1 inhibitors have shown clinical efficacy in many tumors, for example, blockade of PD-1 or PD-L1 with specific antibodies enhances T-cell responses and mediates antitumor activity. However, some cancer patients do not respond well to targeted inhibitors and develop drug resistance, resulting in poor treatment outcomes. In this paper, we review the mechanism of PD-1/PD-L1 blockade in cancer therapy and the application of inhibitors. We hope that in the future, promising combination therapy regimens can be developed to allow immunotherapeutic tools to play an important role in tumor treatment. We also discuss the safety issues of immunotherapy and further reflect on the effectiveness of the treatment and the side effects it brings.